Implikasi Strategi Guru Agama Islam Dalam Meningkatkan Kedisiplinan Terhadap Karakter Baik Siswa Di Madrasah Aliyah Rohani Ikhwanul Muslimin Kecamatan Tebing Syahbandar Kabupaten Serdang Bedagai - Rezeqy, Muhammad Arif; Parinduri, Sari Atika; Muhklis (STAI Tebing Tinggi Deli, 2024)
This study aims to analyze the implications of Islamic religious teachers' strategies in improving students' discipline and good character in Islamic schools. In the context of Islamic religious education, discipline and good character are important aspects that play a role in shaping students' personalities. This study uses a qualitative method with a case study approach in several Islamic schools that implement various educational strategies. Data were collected through interviews with teachers, observations of learning activities, and analysis of documents related to educational policies and practices in Islamic schools. The results of the study indicate that effective Islamic religious teacher strategies include the application of role models, motivational approaches, and the integration of Islamic values ​​​​in the curriculum. The application of role models, where teachers demonstrate good discipline and morals, has a positive impact on student behavior. Motivational approaches that involve rewards and constructive feedback also contribute to improving student discipline. In addition, the integration of Islamic values ​​in every aspect of learning strengthens the internalization of good character.